2010
DOI: 10.1007/s10238-010-0097-2
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of alcohol dehydrogenase (ADH) isoenzymes and aldehyde dehydrogenase (ALDH) measurement in the sera of gastric cancer patients

Abstract: Alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) are present in gastric cancer cells (GC). Moreover, the activity of total ADH and class IV isoenzymes is significantly higher in cancer tissue than in healthy mucosa. The activity of these enzymes in cancer cells is probably reflected in the sera and could thus be helpful for diagnostics of gastric cancer. The aim of this study was to investigate a potential role of ADH and ALDH as tumor markers for gastric cancer. We defined diagnostic sensitivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…The results in the present paper are in agreement with other studies performed on the stomach (Jelski et al, 2010a). Our previous study demonstrated the potential importance of ADH IV as a marker of gastric cancer (GC).…”
Section: Discussionsupporting
confidence: 93%
“…The results in the present paper are in agreement with other studies performed on the stomach (Jelski et al, 2010a). Our previous study demonstrated the potential importance of ADH IV as a marker of gastric cancer (GC).…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have shown that the serum levels of class I ADH are a potential diagnostic marker in multiple cancers, including renal cell,20 brain,21 colorectal,22 endometrial,23 and cervical cancers 24. Similar diagnostic values can also be observed in class III ADH for pancreatic cancer,8 and class IV ADH for esophageal25 and gastric cancers 26. The diagnostic values of ADH isoenzymes in other cancers have not yet been reported, but the difference of ADH isoenzymes between cancer patients and healthy subjects has already been observed.…”
Section: Discussionsupporting
confidence: 63%
“…The ADH isoenzymes generally refer to a metabolic barrier against orally self-administer ethanol and also against ethanol produced from carbohydrates through fermentation of bacterial [14], [15]. ADH1 and ADH2, two well-known members of ADH family, mainly expressed in the liver but also the gastric mucosa, is significantly responsible for the partially metabolism of orally ingested alcohol, namely, in the conversion of ethanol to its carcinogenic metabolite, acetaldehyde, particularly during the elimination phase [16]–[18].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variants in ALDH2/ADH1/ADH2 genes may contribute to alteration in alcohol metabolism which may resulting in the promotion of ethanol oxidation, and may be closely associated with the inhibition of acetaldehyde oxidation, conducing to the accumulation of acetaldehyde [14], [24], [25]. Therefore, it is hypothesized that genetic polymorphisms in the ALDH2/ADH1/ADH2 genes may be strongly correlated with the susceptibility to gastric cancer [16], [26], [27].…”
Section: Introductionmentioning
confidence: 99%